Combined Online-Discussion as a Tool for Formation of Future Engineers’ Reflexion under Conditions of Education Digitalization. - S. A. Mikheev (Высшее образование в России, 2024)
The article analyzes the influence of training based on combined (combining asynchronous and synchronous forms in one pedagogical technology) online discussions (OD) on the formation of reflexion of future engineers. The relevance of the problem is revealed. It is conditioned by toughening requirements to reflexive abilities and network communicative competences of modern technical specialists in the conditions of digitalization of education, networking and socio-technical transformation of engineering activity. The algorithm of realization and stage-role structure of asynchronous and synchronous OD are presented. The four-stage technology of pedagogical application of combined OD combining online-discussions with face-to-face reflexive classes is described, taking into account the mediated nature of learning in the digital environment and psychological features of future engineers related to the specifics of technical thinking. The methodological peculiarities (combination of online discussions with classroom training; stage-role differentiation of online discussions (structuring) on the basis of a scenario plan; use of a facilitation model with partially symmetric interaction of online discussions participants; conducting online discussions in microgroups of 4-6 hours) were identified and the mechanisms of their influence on the effectiveness of combined online discussions in the formation of future engineers’ reflexion were described. Taking into account the above mentioned methodological features, the teacher’s recommendations on the effective organization of the educational process in technical universities on the basis of the developed technology have been formulated. The correlation between the application of the developed technology and the improvement of the subjects’ reflexive skills by 19.67-32.79% was shown and a conclusion was made about its significant role in the formation of a holistic view of the students of technical universities about the discussion as a complex multidimensional category, in which an important role is played by building social interaction with opponents, understanding their position and reaching compromise solutions.